Biologia reprodutiva e da polinização de Physalis peruviana L. - Pavanelo, Anderson Machado (2019)
In this study we described the floral biology of Physalis peruviana L. and investigated the increase in the number of fruits formed and the quality of these fruits through interactions with insects and different modes of manual pollination and also the floral visitors and pollinators. The anthesis was described by measuring floral structures and observing changes in floral whorls, stigma receptivity and anther dehiscence over the duration of the flower. The increase in quality and number of fruits formed was compared between the different modes of manual pollination and control. The frequency of floral visitors (N = 48h), behavior analysis and pollinator definition were made through focal observations. The P. peruviana anthesis lasts three days, with the flower opening and closing each day. During the anthesis, an increase in the size of the stamens (length) and corolla (diameter) was observed. The receptivity of stigma occurs before anthers dehiscence and continues throughout the days of anthesis. The anthers dehiscence is sequential, with an average of three anthers open on the first, all open on the second day. Nectar was produced throughout the anthesis, with available volume between 0,1 and 0,2 microliter, and accumulated volume between 1,8 on the first day and 0,9 microloiter on the third day. The reproductive success in fruit formation in P. peruviana was superior in open pollination (88,46%) when compared to cross-pollination (72,2%) and self-pollination (66,67%). The variables mass, diameter, height and average number of seeds were significantly higher in open pollination and cross pollination when compared to the other tests. Apis mellifera was the most frequent bee in flowers with 98,46% (n = 2302) of visits. There was no pollination deficit in P. peruviana, and although the plant produces fruits by self-pollination, the increase in variables that measure fruit quality and the number of fruits formed was greater in the open pollination test and cross pollination. Thus P. peruviana, considered a self-compatible plant, had its production and fruit quality improved due to the visitation of bees, suggesting that adequate pollination by these insects should be considered in the management strategies for this crop.